To solve the equation \( 13(6x-9) = -33 \), we can follow these steps:
Step 1: Distribute the 13 on the left side.
Step 2: Combine like terms, if necessary, and isolate the term with \( x \).
Step 3: Solve for \( x \).
Applying these steps to your equation:
-
Step 1: Distribute 13. \[ 13 \cdot 6x - 13 \cdot 9 = -33 \] This simplifies to: \[ 78x - 117 = -33 \]
-
Step 2: Add 117 to both sides. \[ 78x = -33 + 117 \] This simplifies to: \[ 78x = 84 \]
-
Step 3: Divide both sides by 78. \[ x = \frac{84}{78} = \frac{14}{13} \]
Now we can check the potential answers given for \( x \):
- \( x = -30 \)
- \( x = -15 \)
- \( x = -22 \)
- \( x = -19 \)
None of these options matches \( \frac{14}{13} \), which is approximately 1.08. There may be an error in the answer choices provided or in the equation. Please double-check the question or the available answer options.
If you need help with something else or further clarification, let me know!